Implementasi Metode MABAC Untuk Menentukan Siswa Yang Layak Menerima Beasiswa PIP SDN - Pasaribu, Haryati; Putri, Raissa Amanda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The MABAC (Multi-Attributive Border Approximation area Comparison) method is a multi-criteria decision making technique that evaluates alternatives based on distance from the border approximate area. This method allows a more objective assessment by considering various criteria and their importance. This research aims to implement the MABAC method in determining students who are worthy of receiving scholarships at SDN 15001 Kolang Nauli 2. Using a Research and Development (R&D) approach with a waterfall model, this research develops a web-based system to process data for 10 sample students based on five assessment criteria. The MABAC method is applied through a series of stages, including forming a decision matrix, normalization, weighting criteria, determining limit values, and calculating alternative distances. The research results show that the system succeeded in implementing the MABAC method accurately, producing objective rankings of scholarship recipient students. Gavin Manuel Hutabarat was selected as the strongest candidate with the highest score of 14,567. This implementation proves the effectiveness of the MABAC method in improving the decision-making process for scholarship allocation, offering a more transparent and measurable solution for schools.